Evaluation of the tangible and intangible heritage resources of the historic center and the first expansion of the city of Limón - García-Baltodano, Kenia (2023)
Heritage is closely related to the territory, and its resources offer the opportunity to generate development based on its capacity to provide job opportunities, promote the availability of services and boost the dynamization of related social sectors. The ethnic and intercultural diversity present in the city of Limón has given it a broad historical, cultural, artistic, and architectural richness that differentiates it from other areas of the country; however, despite the potential they hold, many of these heritage resources are at risk of disappearing. Within the framework of the extension project ‘Taking advantage of opportunities for the generation of endogenous development through the enhancement of heritage resources in the historic center and the first expansion of the city of Limón’, we used participative methodologies for the identification, evaluation, and validation of the city’s principal heritage resources. This article describes the process and the results obtained from this link between the university and the community. The methodology employed was based on participatory action research, a review of documentary sources, interviews, and the use of a multi-criteria evaluation. As a result of the work conducted, we made 76 inventory tabs of the city’s heritage resources. Besides, we evaluated and classified them according to cultural and related domains established by UNESCO. Based on the conclusions drawn, the social stakeholders involved will be able to promote actions to enhance the use of the resources and propose measures for their conservation and enhancement.